2018
DOI: 10.18203/2320-1770.ijrcog20183890
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate dehydrogenase (LDH) level in mild and severe preeclampsia as a prognostic marker

Abstract: Background: Lactate Dehydrogenase (LDH) is mainly an intracellular enzyme. Its level is an useful biomarker for cellular injury which may suggested as a potential marker to predict the severity of preeclampsia and indicator for multi-organ involvement have significant role in management of preeclampsia. We conducted this study to examine the relationship between lactate dehydrogenase concentration and the severity of the disease and occurrence of complications. The objective of the present study was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
1
Order By: Relevance
“…However, the present study and the study conducted by Bairwa et al in 2018 in Rajasthan reported deaths at S. LDH levels of around 600 IU/l as well. 15 Now, though there are various studies in this regard, most of their statistical significance is not proven unlike the present study where the association between S. LDH levels and PNMR is shown to be significant. Strength of the study is that, it provides a basic framework for planning and conducting further studies.…”
Section: Maternal Complicationscontrasting
confidence: 87%
“…However, the present study and the study conducted by Bairwa et al in 2018 in Rajasthan reported deaths at S. LDH levels of around 600 IU/l as well. 15 Now, though there are various studies in this regard, most of their statistical significance is not proven unlike the present study where the association between S. LDH levels and PNMR is shown to be significant. Strength of the study is that, it provides a basic framework for planning and conducting further studies.…”
Section: Maternal Complicationscontrasting
confidence: 87%